Petroleum exploration potential of the Mid-Norway Continental Margin. Issue 2 (May 2020) - Fan, Yuhai; Wang, Hui; Qu, Hongjun; Pan, Chunjuan; Zhang, Gongcheng; Tan, Furong
Abstract: The deepwater basins in the Mid-Norway Continental Margin of North Atlantic continental shelf is one of the hot spots of global petroleum exploration in deepwater area, and its exploration potential is very large. On the basis of synthesizing regional geologic information and the earlier researches of the Mid-Norway Continental Margin, guided by leading edging theories of Reservoir Sedimentology, Petroleum Geology, we found that main source rocks occur in the Upper Jurassic marine shale of Spekk Formation. The main reservoir is shallow marine sandstone of Fangst group of the Middle Jurassic rift stage. Petroleum migration through two ways: petroleum migrate a little distance by means of the cracks, grooming, faults a short distance, and pass through unconformity surfaces or connected sand bodies migrate a long distance, and and eventually into the reservoir. The Mid-Norway Continental Margin is rich in hydrocarbon, its reserve reaches about 73.2 billion barrels of oil equivalent and the undiscovered fields may be up to 36.